The influence of cambered-airfoil on the aerodynamic performance of vertical axis wind turbines - Bausas, Michael D.; Danao, Louis Angelo M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Vertical Axis Wind Turbine (VAWT) has been found to be potentially more efficient and suited for local production of small scale power in the urban areas than horizontal axis wind turbine (HAWT). Since the success of this small wind energy conversion system is largely dependent on maximizing its energy extraction, improving its aerodynamic performance through experimental or numerical analysis is an important task. However, most of the resources on VAWT performance are focused on steady wind analysis rather than unsteady, which is the reaal condition in complex urban terrains. The current study investigated the effect of airfoil asymmetry on the performance of VAWTs through the use Computational Fluid Dynamics modelling. Different configurations of VAWT were achieved by applying various level of camber to a NACA 0025 blade profile, namely: 0.5%; 1.5% (cambered along path of rotation); and 2%. In this reseach, both the steady and unsteady wind VAWT performances were evaluated and the optimum level of blade camber was determined. The research also tried to present an in-depth discussion of the flow physics and wake dynamics, for the two wind cases of VAWTs, through flow visualizations and blade force analysis. Steady results revealed that incorporating a positive level of blade camber to VAWT design can improve its overall performance. Specifically, the most favourable level for VAWT application is the one with the camber line along the path of rotation. These observations were found to be true for the unsteady wind case as well. However, the fluctuating wind seemed to marginally induce detrimental effect to VAWT performance as the cycle-averaged CP for this case becomes slightly lower than the optimum staedy CP at relatively the same tip speed ratio. Generally, the unsteady CPs greatly vary with the fluctuating wind and do not follow the steady performance curve of the VAWTs.
Thesis (M.S. in Energy Engineering)--University of the Philippines Diliman
Keywords: Vertical axis wind turbines; Wind turbines -- Aerodynamics; Camber (Aerofoils).